Mysticism, mind, consciousness - Forman, Robert K. C. (Albany, NY : State University of New York Press, 1999)
"In an exploration of mystical texts from ancient India and China to medieval Europe and modern day America, Robert K.C. Forman, one of the leading voices in the study of mystical experiences, argues that the various levels of mysticism may not be shaped by culture, language and background knowledge, but rather are a direct encounter with our very conscious core itself." "Mysticism, Mind, Consciousness focuses on first-hand accounts of two distinct types of mystical experiences. Through examination of texts, recorded interviews, and courageous autobiographical experiences, the author describes not only the well-known "pure consciousness event" but also a new, hitherto uncharted "dualistic mystical state." He provides a thorough and readable depiction of just what mysticism feels like. These accounts, and the experiences to which they give voice, arise from the heart of living practices and have substance and detail far beyond virtually any others in the literature."--Jacket
Mystics and constructivists -- The pure consciousness event -- Reports of pure consciousness events -- Of horses and horses carts -- Non-linguistic mediation -- Buddhists and constructivism -- A new model for pure consciousness -- Of horse carts and space capsules constructive language and spiritual techniques -- Knowledge by identity -- The dualistic mystical state -- Silence, thinking, and cutting carrots characterizing an advanced mystical state -- The Janus-faced soul an epistemology of the dualistic mystical state -- Concluding remarks.
Includes bibliographical references (pages 201-209) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Mysticism; Mysticism; Mysticisme; mysticism; RELIGION -- Mysticism; Mysticism